Sulfonamide-1, 3, 5-triazine–thiazoles: discovery of a novel class of antidiabetic agents via inhibition of DPP-4. Issue 86 (2nd September 2016) - Gao, Hai-De; Liu, Peng; Yang, Yang; Gao, Fang
Abstract : Dipeptidyl peptidase-4 (DPP-4) inhibitors are a novel class of antidiabetic drugs used for treating type 2 diabetes mellitus. Abstract : Dipeptidyl peptidase-4 (DPP-4) inhibitors are a novel class of antidiabetic drugs used for treating type 2 diabetes mellitus. In the present study, a novel hybrid sulphonamide-1, 3, 5-triazine–thiazole derivatives were synthesized and characterized by 1 H-NMR, 13 C-NMR, FT-IR, mass spectroscopy and elemental analysis. The result showed that among the tested compounds, 8c was found to be a more potent inhibitor of DPP-4 (2.32 nM) than the alogliptin standard. Moreover, molecular docking results showed that ligand8c was efficiently docked into the active site of the catalytic triad of Ser630, Asp708 and His740, encompassing both the S1 and S2 pocket with a CDOCKER interaction energy of 57.80. The in vitro results were further substantiated by in vivo blood glucose lowering effects in experimental subjects. The results of the investigation showed that compound8c exhibited concentration-dependent improvement of glucose tolerance in ICR after oral administration. It has been also found that compound8c (30 mg kg −1 ) showed a reduction in the area under the curve from 0 to 120 min [(AUC) 0–120 min] to 37.46%, which was found to be approximately similar to the hypoglycemic profile of alogliptin (standard). The activity of compound8c was also investigated in STZ-induced diabetic rats where it showed a dose-dependent decrease in blood glucose levels together with an improvement in insulin levels probably via inhibition of DPP-4. The effect of compound8c was also investigated on the lipid profile and antioxidant enzyme system.